Study of Fermentation Strategies by Lactobacillus gasseri for the Production of Probiotic Food Using Passion Fruit Juice Combined with Green Tea as Raw Material - Wanessa Dayane Leite Lima; Shênia Santos Monteiro; Matheus Augusto de Bittencourt Pasquali (Foods, 2022)
Foods fermented by Lactobacillus with probiotic properties convey health benefits to consumers, in addition to fulfilling the basic function of nourishing. This work aimed to evaluate the growth characteristics of L. gasseri in passion fruit juice and passion fruit added with green tea. Fermentation under evaluation of different pH (3.5–7.5), temperature (30–44 °C), and with the addition of green tea (7.5–15%), took place for 48 h. The results showed that a pH of 7.5 and temperature of 44 °C showed higher cell production, and it was also verified that the addition of 15% of green tea induced the growth of L. gasseri in passion fruit juice. The concentrations of probiotic cells observed were above 9 Log CFU.mL−1 and, therefore, they are promising products for consumption as a functional food and application in the food industry with potential health benefits.